Changes to Antibiotic Use After the Introduction of an Antimicrobial Stewardship Program in a Neonatal Intensive Care Unit. (1st June 2016) - Leifso, K; Dow, K; McKnight, S; Sheth, P; Tomalty, L
Abstract: BACKGROUND: Inappropriate or prolonged antibiotic use in neonatal intensive care units can lead to the emergence of antibiotic resistant bacteria as well as complications such as invasive candidiasis and necrotizing enterocolitis. An antimicrobial stewardship program (ASP) was introduced in our level II/III neonatal intensive care unit (NICU) with the goal of optimizing patient safety and outcomes with respect to antimicrobial use as well as to reduce the risk of infection or colonization by antimicrobial resistant organisms (AROs). The ASP included a pediatric infectious diseases physician, a neonatologist or delegate, a microbiologist and a pharmacist who met twice weekly to review all admitted neonates who had been receiving antibiotics for more than 24 hours. OBJECTIVES: In order to evaluate the effectiveness of ASP interventions, we conducted a retrospective review of antibiotic use in the NICU comparing the two years before the ASP and the first year of the ASP operation. DESIGN/METHODS: Antimicrobial use from the two years prior and one year following the ASP start date of December 1st, 2014 was compared. All neonates who received antimicrobials between the dates of December 1st, 2012 and November 30th, 2015 were included in the review. Antifungal and antiviral use were excluded. Antibiotic start and stop dates were collected from the patient charts. After the start of the ASP, antibiotic start and stop dates were obtained from the computerized pharmacy database. Overall days of therapy (DOTs) and antibiotic-specific DOTs, were calculated per 1000 patient-days. RESULTS: In the first year, 109 reviews were performed on 70 neonates. The pediatric ID service was already following 25 babies leaving 84 reviews. Changes were recommended in 43 (51%) instances. Discontinuation of antibiotics was recommended in 26 (60%), reduced length of therapy or decreased spectrum of antibiotic in 10 (24%), and ID consultation in 9 (21%). Overall and selected antibiotic exposure in the NICU is presented in Table 1 (See page e79). CONCLUSION: Introduction of an ASP reduced the overall exposure to antimicrobials in the NICU. Marked reductions in third-generation cepha-losporin and vancomycin use were observed in the first year of the ASP.